2017
DOI: 10.3390/ma10050469
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Study of the Effect of Ba2+ Cations Substitution with Sr2+ Cations on Structural and Optical Properties of Ba2−xSrxZnWO6 Double Perovskite Oxides (x = 0.00, 0.25, 0.50, 0.75, 1.00)

Abstract: The effect of Sr2+ substitution on the morphology, crystal structure, and optical properties of double perovskite oxide Ba2−xSrxZnWO6 (x = 0.00, 0.25, 0.50, 0.75, 1.00) were investigated. Scanning electronic microscopy demonstrated that all samples have similar microstructure morphology but differ in the range of grain sizes. X-ray diffraction measurements indicated that these materials crystallize in a (Fm-3m) cubic crystal structure, and also confirmed the tolerance factor. Rietveld analysis revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…About the same time, Bugaris et al [ 38 ] reported the optical properties of crystals of cubic DP Ba 2 MgWO 6 and Ba 2 ZnWO 6 grown by a flux method, along with structural refinement. Alsabah et al [ 39 ] studied the effect of different concentrations of Sr 2+ ions on the structural and optical properties of BaZnWO 6 DP oxides. Later, Chen et al reported the PL properties of Ba 2 ZnWO 6 :Eu 3+ , Li + [ 40 ] in 2017 and Ba 2 ZnWO 6 :Sm 3+ [ 41 ] in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…About the same time, Bugaris et al [ 38 ] reported the optical properties of crystals of cubic DP Ba 2 MgWO 6 and Ba 2 ZnWO 6 grown by a flux method, along with structural refinement. Alsabah et al [ 39 ] studied the effect of different concentrations of Sr 2+ ions on the structural and optical properties of BaZnWO 6 DP oxides. Later, Chen et al reported the PL properties of Ba 2 ZnWO 6 :Eu 3+ , Li + [ 40 ] in 2017 and Ba 2 ZnWO 6 :Sm 3+ [ 41 ] in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 showed the XRD parameters of Zn 0.5 Li 2x Mg 0.5-x Fe 2 O 4 nanopowder, also it described the relation between the rated molar of lithium concentration and structure parameters of samples, that noticed the increase of lattice parameter(a) from 8.379 to 8.408 Å of a sample by increasing the molar of lithium cations, whereas Li 1+ ionic radius is less than Mg 2+ cations radii. The crystallite size of samples was calculated by Debye-Scherrer equation [15] [16].…”
Section: Xrd Resultsmentioning
confidence: 99%
“…All ferrite nanoparticles properties are dependent on the cations nature, charges and their distribution through the tetrahedral (A) and octahedral (B) sites [14]. Different preparation methods have been followed to accomplish nanoferrite particles such as solid-state reaction method [15] [16], hydrothermal method [17], sol-gel method [18], co-precipitation route [19], and Chemical combustion route [20]. The chemical co-precipitation route could be the most synthesized method for Mg, Co and Zn Nano-ferrite.…”
Section: Introductionmentioning
confidence: 99%
“…The Maud program was used for XRD analysis, with the Rietveld refinement method. The crystalline size (D) was calculated by Scherer's equation [33]:…”
Section: Characterizationmentioning
confidence: 99%